Determinación del potencial de captura de carbono en cinco especies forestales de dos años de edad, cedro nativo, (Cederla Odorata) Caoba, (Swietenia Macrophylla) Bolaina, (Guazuma Crinita) Teca, (Tectona Grandis) y Capirona, (Calycophyllum Sprucearum) en la localidad de Alianza San Martín 2009 - Quitoran Dávila, Gerald Felipe (2010)
At the meeting in Rio de Janeiro, Brazil: Eco-92, signed the Framework Convention on Climate Change, signed by 162 heads of state, widely expected by fields of science, political and social (IUCC, UNEP, 1995; Framework Convention on Climate Change, 1998). But that legislation opening a space for discussion that the subject warranted in Agenda 21 (UNEP, 1996). The measures to implement, are the product of multidisciplinary research and periodic reports issued by the IPCC, Intergovernmental Panel on Climate Change (IPCC, 1995) the macro political wing is given by the Conference of the Parties (COP), a forum in regular meetings, proposes and monitors implementation of technical tips, and some of its products: the mantle of Berlin 93 and the Kyoto Protocol 97 (CMNUCO, 1997; Parlamento Latinoamericano, et al, 1998). There are also several other discussion groups, funding and related actions: the Forum for the Global Environment Facility (GEF). The alliance of small island states (SIDS), the World Meteorological Society (SMM), the program of the United Nations Environment Program (UNEP), among the most important (IPCC, 1995; UNEP, et al. 1999) Alternatively, there is global convergence, which is essential to generate new paradigms of development and behavior (individual and social) supported by precepts of sustainability and equity, this particular point of urgent applicability (CMNCO, 1997). Suggested lines considered: emission inventories, mitigation programs, basic research, promoting research, technology transfer, promotion and protection of sinks, exchange of information and citizen participation (Latin American Parliament, et al. 1998. Politically, in Kyoto 97 has proposed concrete measures, such as reducing emissions to levels unprecedented generation of international markets, providing knowledge, information, technology and financing north - south (Latin American Parliament et al. 1998) but the response has been uneven, to the point that protocol will remain even without ratification. have proved most successful negotiations of emission quotas that involves not only states but private organizations as intermediaries in this "market of tradeable emission rights" has even established a valuation fee "carbon dioxide equivalent "(Ortiz et al 1998 Latin American Parliament et al, 1998) The potential for carbon sequestration through afforestation / reforestation depends on the species, location and management system and therefore is highly variable. The normal rates of absorption, expressed in tonnes of carbon (tC) per hectare per year, and in the tropics is 3.2 to 10 tC (Bronwn, 1996). Studies in tropical regions indicate that a volume could absorb additional carbon, which is estimated at 11.5 to 28.7TC through regeneration of about 217 million ha of degraded land. Perhaps only one third of the earth may be earmarked for environmentally sound afforestation / reforestation (Houghton, et al. 1991). Studies of native species have been a great contribution, but are still relatively recent and scarce to allow making decisions about the use of these species to larger-scale reforestation programs. However, the preliminary experiences in the world demonstrated the potential to possess many of these native species in the tropics mainly